EFFICACY OF COROSOLIC ACID ON MITOCHONDRIAL ENZYMES AND DNA DAMAGE AGAINST CCL4-INDUCED HEPATOTOXIC RATS - Abdullah H. Al-Assaf (Journal of Animal and Plant Sciences, 2014)
The present study is aimed to evaluating the protective effect of corosolic acid (CRA) on mitochondrial enzymes and DNA damage in carbon tetrachloride (CCl4)-induced hepatotoxic rats. The activities of hepatic mitochondrial enzymes such as isocitrate dehydrogenase (ICH), α-ketoglutarate dehydrogenase (KDH), succinate dehydrogenase (SH), malate dehydrogenase (MDH), NADPH dehydrogenase and cytochrome C oxidase were significantly decreased in CCl4-hepatotoxic rats, and administration of corosolic acid brought back these parameters towards normal. The lipid peroxidative index in hepatic mitochondrial fractions was increased in CCl4-treated groups, which were decreased significantly on treatment with CRA. The antioxidants, which were depleted in CCl4-treated groups, were improved significantly by CRA. An increase in the severity of DNA damage was observed in liver mitochondrial fractions of CCl4 induced rats. Pretreatment with CRA shows a significant decrease in tail length and tail moment of comet. Thus, the results demonstrate that CRA has potent antioxidant properties, improves mitochondrial enzymes and protective effect against DNA damage in CCl4 induced liver damage in rats.
Keywords: Hepatotoxicity; carbon tetrachloride (CCl4); corosolic acid; DNA damage